Architecture of the world's major religions : an essay on themes, differences, and similarities - Barrie, Thomas (Brill research perspectives., 2020)
In Architecture of the World's Major Religions: An Essay on Themes, Differences, and Similarities, Thomas Barrie presents and explains religious architecture in ways that challenge predominant presumptions regarding its aesthetic, formal, spatial, and scenographic elements. Two positions frame its narrative: religious architecture is an amalgam of aesthetic, social, political, cultural, economic, and doctrinal elements; and these elements are materialized in often very different ways in the world's principal religions. Central to the work's theoretical approaches is the communicative and discursive agency of religious architecture, and the multisensory and ritual spaces it provides to create and deliver content. Subsequently, mythical and scriptural foundations, and symbols of ecclesiastical and political power are of equal interest to formal organizations of thresholds, paths, courts, and centers, and celestial and geometric alignments. Moreover, it is equally concerned with the aesthetic, visual and material cultures and the transcendent realms they were designed to evoke, as it is with the kinesthetic, the dynamic and multisensory experience of place and the tangible experiences of the body's interactions with architecture.